Efforts to Improve The Social Skills of Elementary School Students Through Modified Traditional Crank Games - Abdullah Efendi; Muh Muhaimin; Hamidaturrohmah Hamidaturrohmah (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
The social skills of today's youth are a problem that requires attention, as mobile phones and smartphones are now among the media on which kids spend their free time. The impacts of youngsters playing modern games frequently on handheld devices or other technology lead a child's social level to decline, therefore witnessing this phenomena worries us. The findings of the observations done at SD Negeri 3 Meganti show that children prefer independent activities, that they are challenging to control, that they like to quarrel, and other things. This study aims to determine whether modified versions of conventional hopscotch games might help kids develop their social skills. 20 students from class II of SD Negeri 3 Menganti participated in this study, which used the classroom action research method and the Kemmis &; Taggart model. Four stages of research were carried out, including planning, activity, observation, and reflection. The outcomes demonstrated an improvement in the social skills of class II students at SD Negeri 3 Menganti. Average student learning results from Cycle I were just 15.5%, but after being exposed to the action of a modified classic crankshaft game in Cycle II, there was a notable improvement to average student learning outcomes of 25.5%.